An Ideal Marriage: A Study of the Marriage Sermon in the Perspective of Gadamer’s Hermeneutics - Lutfi, Mochtar; Mohammad Adib; Manuaba, Ida Bagus Putera (Universitas Airlangga, 2024)
This paper aims to find a dynamic relationship between the text and the interpreter in the marriage sermon. This dynamic is explored by utilizing qualitative methods with the Gadamer’s Hermeneutics approach, which focuses on the acceptance of listeners or readers rather than the speaker's intent. There are two parties involved in understanding: the horizon of the text and the horizon of the interpreter. Gadamer's hermeneutics illustrates hermeneutics as a fusion of horizons. Hermeneutics is an attempt to clarify the conditions for understanding to take place. Thus, the meaning of the text is no longer limited to the author's intent but is open to the interpretation of the reader. There is a dynamic relationship between the horizons of the text and the horizons of the interpreter. Brides and families receive marriage advice when arranging paperwork at the Office of Religious Affairs, ordering material from the khatib to be delivered during the marriage sermon, and the atmosphere at the ceremony venue supports understanding the horizon of the text with the horizon of the interpreter. Therefore, the fusion of horizons of the text and the interpreter of the marriage sermon from the perspective of Gadamer's Hermeneutics shows the formation of a prosperous, happy, and noble family, in line with the concepts of sakinah, mawaddah, and warrahmah.